Construction and validation of the quality of oncology nursing care scale (QONCS) - Charalambous, Andreas (BMC Nurs, 2014)
BACKGROUND: There is scarcity of questionnaires specifically on the quality of the nursing care provided to patients diagnosed with cancer. The available questionnaires have been developed without attributing a holistic approach to the care provided with important patient’s needs remaining without assessment. The main aim was to develop a self-administered cancer specific questionnaire exploring patients’ views on quality nursing care provided in oncology settings. METHODS: The development of the scale proceeded through three phases. As part of the first development phase areas of concern and items of interest were identified through a literature review. The second phase included a pilot study of the QONCS and a subsequent validation phase through a multicentre study in 3 hospitals, 4 departments and 418 patients diagnosed with cancer and receiving care as inpatients. The study was designed to select items, identify dimensions, measure reliability, content and construct validity. RESULTS: The QONCS consisted of 34 items. A factorial analysis grouped the items into five categories that define quality nursing care: a) Being supported and confirmed, b) Spiritual caring c) Sense of belonging, d) Being valued and e) Being respected. Cronbach’s alpha was 0.95 for the entire questionnaire. The factor solution explained 68.53% of the variance. CONCLUSIONS: QONCS appears to measure with adequate reliability and validity the attributes of quality nursing care within the oncological settings and to patients with a variety of cancer diagnoses and at different phases of the cancer trajectory. The instrument is quick to disseminate and easy to complete, making it a suitable instrument for nursing professionals to evaluate patients’ self-perceived quality of nursing care as a mean to promote the quality of the care provided in oncological settings.